Effect of high intensity ultrasound on the milk fermentation by bifidobacteria - Anamarija Ljubić; Anita Jurić; Katarina Lisak Jakopović (Mljekarstvo)
Treating food by ultrasound is a relatively novel food processing method which has been developed in the last two decades. When considering milk processing, ultrasound might be used to reduce the count of harmful microorganisms, and to stimulate the growth of probiotic bacteria during milk fermentation, especially bifidobacteria. The most commonly used probiotic cultures in fermented dairy products are bifidobacteria. The main problem related to the fermentation by bifidobacteria is that milk does not provide a natural environment for their growth and survival. Thus the application of bifidobacteria in milk fermentation is limited. Many studies indicated that the application of high intensity ultrasound (20 kHz) may shorten the duration of milk fermentation by B. infantis, B. brevi and B. animalis subsp. lactis. Also, studies showed that the stimulating mechanism of bifidobacteria growth by ultrasound was associated with the kinetics of carbohydrates and organic acids during fermentation. The aim of this review was to demonstrate how the application of the high intensity ultrasound stimulates the growth of bifidobacteria in the milk, and thus improves the fermentation process.